The Effect Of Trust, Quality Of Service, And Location On Student Loyalty Through Student Satisfaction At Sma Citra Alam Ciganjur Jakarta Selatan - Qoyum Nur Safitri; Andini Nurwulandari (Institute of Computer Science (IOCS), 2022)
The purpose of this study was to determine the effect of trust, service quality, and location on student loyalty and to determine student satisfaction in intervening the relationship between trust, service quality, and location on student loyalty. The population of this research is all SMA Citra Alam Ciganjur Jagakarsa, South Jakarta. Data were collected as many as 161 respondents and processed with IBM AMOS software version 22. Based on the research results obtained empirical facts in the form of: 1) Trust directly has a positive effect on Student Satisfaction; 2) Service quality directly has a positive and significant effect on student satisfaction; 3) Location directly has a positive and significant effect on Student Satisfaction; 4) Student Satisfaction directly has a positive and significant effect on Student Loyalty: 5) Trust indirectly has a positive and significant effect on Student Loyalty through Student Satisfaction; 6) Service quality indirectly has a positive and insignificant effect on Student Loyalty through Student Satisfaction; 7) Location indirectly has a positive and significant effect on Student Loyalty through Student Satisfaction.